Building Maintenance Management for Steel Structures in Industrial Facilities. Issue 3 (16th September 2019) - Hemker, Andreas; Bartenbach, Jochen; Dürr, André
ABSTRACT: The building infrastructure in Europe is becoming older and older. Steel structures in industrial facilities and plant constructions are also affected by this ageing process. With a Building Maintenance Management (BMM) program it is possible to prevent the reduction of the load‐bearing capacity of the structure with increasing age. Repair and remediation costs can also be reduced if defects are detected by BMM in time. In Germany guideline VDI 6200 (1) provides a framework for the procedure of BMM pertaining to public buildings as well as industrial and plant buildings, but it does not take into account the type of construction. The special characteristics of steel structures such as those found in industrial prefabrication, with minor variations in the execution, or the generally favourable accessibility of critical joints and the time‐dependent corrosion effects are, therefore, not considered within the procedures of BMM in guideline VDI 6200 (1). HOCHTIEF Engineering has gained a wealth of experience in recent years with regard to steel structures in industrial facilities and plant constructions through the BMM program. Within this paper the special issues for these steel structures in BMM are summarized. The main focus lies in the implementation of a BMM program for these steel structures and in the preparation of regular inspections by experts according to the type of structure. In addition, typical defects and remediation measures for industrial steel structures are compiled and presented within this paper.